Urgensi Pendidikan Prenatal dalam Prespektif Islam - Tiya Latipah; Undang Ruslan Wahyudin; Taufik Mustofa (AS-SABIQUN, 2022)
Parents are the most important and first educators for a child, because children receive the first education from children. Mothers and fathers play an important and very influential role in the development of children. The mother stayed with him because the child remained in the womb until delivery. Therefore, he imitates the temperament of the mother, and the child usually loves the mother more. As we know, mothers are the first madrasa or school for their children. Likewise, the father's influence is immense, and he is a major helper and a character greatly admired for his toughness and wisdom in dealing with the subject. Fathers have an important role in the development of children. Islam goes very well like family education and its main goal is to create a generation of noble character. To achieve this, the family, especially parents, is the first foundation of a child's basic education. Basic education is the education that a mother receives during pregnancy (before giving birth). This study aims to explain the importance of prenatal education from an Islamic perspective. This search is a qualitative descriptive literature search. The data collection technique in this case is to identify discourses from books, articles, magazines, the Web (Internet) or other information. The data analysis method used is content analysis. The results of this study indicate that Islam is very concerned about prenatal education and instilling good values so that it becomes the basic capital for the development of subsequent life. Islam commands all parents to pay attention to every movement of their behavior during pregnancy. Both in the way children are raised and the material given to children as the first environment that children receive.